Modelling, Simulation and Flight Test of a Model Predictive Controlled Multirotor with Heavy Slung Load. Issue 17 (2016) - Notter, S.; Heckmann, A.; Mcfadyen, A.; Gonzalez, F.
Abstract: A controller for stable flight and precise tracking of a multirotor unmanned aerial vehicle (UAV) carrying a heavy slung load is presented within this paper. A novel mathematical model for the multi-body system is derived. Based on that model, a Model Predictive Control (MPC) scheme is designed and applied to the system. Stability and tracking ability are demonstrated through numerical simulation. The performance of the system using the MPC strategy is compared to a linear-quadratic regulator (LQR) control approach. The simulation results are then verified by real flight tests, whereby the MPC is applied to a real multirotor UAV with a heavy slung load. The system is capable of actively damping load oscillations whilst simultaneously tracking a reference trajectory.